The Effect of Prematurity on Children's Cognitive and Psychomotor Development - Purnomosari, Lupi; Opan Fadilah, Muhamad (Ridwan Institute, 2024)
Development is something that must occur in living things, including humans. The development that occurs in a child is cognitive and psychomotor development. However, there are several factors that hinder development, one of which is being born prematurely. The purpose of this study was to determine the effect of prematurity on children's cognitive and psychomotor development. The research method used in this research is a literature review with a qualitative approach. The data collection technique is done with documentation. So that the data source used is secondary data. After the data is obtained, data analysis is carried out with Miles & Hubberman interactive analysis through three stages, namely data reduction, data presentation, and conclusion drawing. It was found that prematurity has a significant impact on the development of children's cognitive and psychomotor development as their organs are not fully developed, leading to the risk of complications and impairment of these abilities. So, the importance of cognitive and physical stimulation programs to support the optimal development of children born prematurely